Optimizing of selective catalytic reduction urea injection and NOx conversion analysis of diesel engine based on higher-order physical model and sequential quadratic programming algorithm - Liu, Wenlong; Gao, Ying; You, Yuelin; Jiang, Changwen; Hua, Taoyi; Xia, Bocong (Energy (Oxford), 2024)
In order to maximize the NOx conversion rate and minimize NH3 slip in the diesel selective catalytic reduction (SCR) system, first, the high-order SCR model was simplified and solved using the trapezoidal method and second-order backward difference formula, while the chemical reaction parameters were optimized using the Gauss-Newton method. The results of the engine bench test show that the mean absolute errors of NH3 and NOx concentrations under steady-state operating conditions were 2.67 ppm and 1.72 ppm, respectively, and 5.46 ppm and 42.50 ppm under severe operating conditions. Second, urea injection rate is optimized based on a high-order model combined with the sequential quadratic programming (SQP) algorithm. The change in NOx conversion rate at different temperatures and space velocities is analyzed, and the results show that the NOx conversion is best at 650 K and 29,000 h⁻1. Third, the experiment validation show that the optimal NH3/NOx ratio is 0.69 at 554 K and 54,200 h⁻1; 0.8; and 1.37 at 746 K and 116,700 h⁻1. Finally, this paper simulates and analyzes the SCR emission characteristics at different temperatures and space velocities when the upstream NOx concentration is 1000 ppm. •The high-order SCR model combined with SQP is proposed for optimizing diesel engine SCR urea injection for the first time.•The TR-BDF2 method is used to solve the high-order SCR model, and the Gauss-Newton method is employed to optimize its chemical reaction parameters.•The SQP algorithm calculates the optimal upstream NH3/NOx ratio for the full load of the engine.•The method ensures high NOx conversion while limiting NH3 slip.